Monetary Commitment and Structural Reforms – A Dynamic Panel Analysis for Transition Economies - Ansgar Belke; Lukas Vogel (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper examines the contemporaneous relationship between the exchange rate regime and structural economic reforms for a sample of CEEC/CIS transition countries. We investigate empirically whether structural reforms are complements or substitutes for monetary commitment in the attempt to improve macroeconomic performance. Both EBRD and EFW data suggest a negative relationship between flexible exchange rate arrangements and external liberalization. Another finding from the EFW sample is that economic liberalisation has tended to be stronger under better macroeconomic fundamentals, suggesting that the impact of good macroeconomic conditions as facilitating structural reforms outweighs countervailing effects in the sense of lower reform pressure. – – Dieser Beitrag untersucht den Zusammenhang zwischen dem Wechselkurssystem und strukturellen Reformen für zentral- und osteuropäische Staaten. Es wird empirisch geprüft, ob strukturelle Reformen Komplemente oder Substitute für die geldpolitische Verpflichtung zu einer verbesserten Makropolitik sind. Sowohl Daten der Europäischen Bank für Wiederaufbau und Entwicklung als auch der Economic Freedom of the World-Index weisen auf eine negative Beziehung zwischen flexiblen Wechselkursen und außenwirtschaftlicher Liberalisierung hin. Darüber hinaus zeigen die Ergebnisse, dass wirtschaftliche Liberalisierung positiv von den makroökonomischen Fundamentaldaten abhängt. Insofern scheint eine gute makroökonomische Performance strukturelle Reformen zu erleichtern und sogar den Effekt eines geringeren Reformdrucks auszugleichen.
Keywords: D78; E52; E61; F36; 330; Exchange rate regime; structural reform; panel data; political economy of reform; transition countries